Dynamic Causality between Energy Consumption and Non-oil gas Economic Growth in Indonesia - Dewi PUSPANINGRUM; Aliasuddin; Nazamuddin (Communications of International Proceedings, 2020)
This study aims to examine the dynamic causality relationship between energy consumption and nonoil-gas economic growth in Indonesia. ARDL and Granger-Causality model are used in this study for the annual data for the period from 1988 to 2018, or total samples are 31 years. The results show that energy consumption has a positive and long-run effect on nonoil-gas economic growth in Indonesia, vice versa. The effect of energy consumption on nonoil-gas economic growth than the effect of nonoil-gas economic growth on energy consumption. Besides, energy consumption has a short-run effect on nonoil-gas economic growth, and causality is a one-way direction. This means that energy consumption is crucial for nonoil-gas economic growth both in the short-run and in the long-run. Because energy consumption is essential to the Indonesian economy, it is recommended to provide green energy to support further economic growth as well as environmental protection.
Keywords: Energy Consumption; Nonoil-Gas Economic Growth; ARDL; Granger Causality.